Anatomical Variations in Patients with Ménière Disease: A Tomography Study - Lucinda, Lucas Resende; Cristoff, Daniela Dranka; Coelho, Luiz Otávio De Mattos; Zanini, Otávio Pereira Lima; Guimarães, Rita De Cassia Cassou (International Archives of Otorhinolaryngology, 2018)
Introduction The etiology of Ménière disease (MD), a difficult-to-treat condition with great morbidity, remains controversial in the literature. The possible clinical and diagnostic impact of anatomical variations of the temporal bone among patients with MD has been recently studied.Objective To identify anatomical variations of the temporal bone associated with the diagnosis of MD.Methods Thirty-seven patients were included, although each ear was considered separately (n = 74). A case group (nA = 33) was composed of the affected ears of patients with definite MD and a control group (nB = 41) was used consisting of the ears of individuals who did not meet the criteria for MD and of the contralateral ears from patients with unilateral disease. Tomographic images from the individuals included in the study were submitted to a blinded and systematic evaluation regarding a broad variety of anatomical variations of the temporal bone. Obtained data were compared statistically between the groups and after stratifying the study sample. Significance level was set at 0.05.Results Among the affected ears, it was observed an increased number of tomographic scans in which the vestibular aqueduct could not be identified (p = 0.01, Fisher exact test). No statistically significant differences were observed when comparing the affected and contralateral ears from patients with unilateral MD, between affected ears from patients with unilateral and bilateral disease or between contralateral ears of patients with unilateral affection and patients without the disease.Conclusion Some anatomical variations might be more frequent in the affected ears of patients with MD, such as the lower rates of individualization of the vestibular aqueduct.
Keywords: Ménière disease; temporal bone; x-ray computed tomography